Alternative Medicines on the Farm: A Study of Dairy Farmers' Experiences in France - Hellec, Florence; Manoli, Claire; Joybert, Manon de (Frontiers in Veterinary Science, 2021)
Despite being of debatable efficacy, alternative medicines are in regular use on both organic and conventional dairy farms as a means of limiting the on-farm use of antibiotics. The study presented here examined French dairy farmers’ understanding of and experiences with these medicines, focusing on homeopathy, aromatherapy, and herbal remedies. Adopting an interdisciplinary approach combining animal science and sociology, we considered how dairy farmers’ use of alternative medicines fits into a holistic approach to herd health management, on the one hand, and into farmers’ networks of professional relationships, on the other. Our findings show that farmers are interested in alternative medicines for reasons that are at once technical, ethical, and economic. In the absence of local veterinarian specializing in homeopathy and aromatherapy, farmers enroll in short-term training courses to learn how to use these medicines. Alternative medicines are not a substitute for conventional medicine for these farmers; rather, they constitute one part of a holistic approach to herd health that combines preventive measures with a variety of curative treatments, and which is grounded in close attention to the animals’ state of health. Farmers make use of guidelines for observing livestock that are central to the veterinary alternative medicine approach. Interestingly, women farmers appear to play an important role in introducing these practices into the management of the farm operation. Finally, farmers’ interest in alternative medicines is indicative of their broader expectations for advice and support in moving toward the integrated management of livestock health, a key element of the agroecological transition. Recognizing these expectations offers useful insights for rethinking the role of veterinarians in dairy farming.